2012
DOI: 10.1177/0091270011400604
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibitors: A New Emerging Therapeutic Class in the Treatment of Type 2 Diabetes Mellitus

Abstract: The incidence of type 2 diabetes mellitus is increasing worldwide. The existing therapeutic classes of antidiabetic drugs are not adequately effective in maintaining long-term glycemic control in most patients, even when used in combination. One emerging novel therapeutic class of antidiabetic drugs is sodium glucose cotransporter 2 (SGLT2) inhibitors. SGLT2 accounts for 90% of the glucose reabsorption in the kidney. The SGLT2 inhibitors increase urinary excretion of glucose and lower plasma glucose levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 27 publications
0
45
1
Order By: Relevance
“…However, once diabetes has developed, the chronic existence of hyperglycemia (glucotoxicity) may contribute to the vicious cycle, which worsens insulin resistance and glucose effectiveness, and may lead to diabetic complications (40). Therefore, breaking the vicious cycle by correcting hyperglycemia with a SGLT2-I is likely to be an attractive strategy to ameliorate diabetes (1,17). On the other hand, since in insulin-resistant diabetic patients (48) and animals (12, 47) hyperglycemia compensates for insulin resistance and glucose intolerance to allow utilization and storage of absorbed glucose at nearly normal levels, one might be concerned that the SGLT2-I strategy, which normalizes hyperglycemia by discarding glucose into urine, might impair carbohydrate storage in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, once diabetes has developed, the chronic existence of hyperglycemia (glucotoxicity) may contribute to the vicious cycle, which worsens insulin resistance and glucose effectiveness, and may lead to diabetic complications (40). Therefore, breaking the vicious cycle by correcting hyperglycemia with a SGLT2-I is likely to be an attractive strategy to ameliorate diabetes (1,17). On the other hand, since in insulin-resistant diabetic patients (48) and animals (12, 47) hyperglycemia compensates for insulin resistance and glucose intolerance to allow utilization and storage of absorbed glucose at nearly normal levels, one might be concerned that the SGLT2-I strategy, which normalizes hyperglycemia by discarding glucose into urine, might impair carbohydrate storage in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the limitations and side effects of these agents have spurred the research in optimizing metabolic control by specifically targeting renal glucose reabsorption through pharmacological inhibition of the sodium glucose cotransporter type-2 (SGLT-2). SGLT-2 is almost entirely confined to the early segment of the renal proximal tubule, where it mediates reabsorption of most of the filtered glucose (Ghosh et al, 2012). Many T2DM patients show increased glucose reabsorption, which may be associated with upregulated SGLT-2 function (Rahmoune et al, 2005), thus further suggesting the feasibility in targeting SGLT-2 function to control hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increase in urinary glucose excretion leads to a negative energy balance and osmotic diuresis, making it a unique antidiabetic agent that reduces also body weight and blood pressure in diabetic patients (Abdul-Ghani and DeFronzo, 2008;Nair and Wilding, 2010). Several SGLT2-selective inhibitors are in various stages of clinical trials (Hussey et al, 2010;Sha et al, 2011;Grempler et al, 2012;Shah et al, 2012), and proof-of-concept has been reported with dapagliflozin (Forxiga; Bristol-Myers Squibb, NY), in phase III studies in patients with T2DM (Bailey et al, 2010;Ghosh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%